Aplikasi Health Belief Model Terhadap Perilaku Preventif COVID-19 pada Kelompok Lansia - Fitriani, Fitriani; Farisni, Teungku Nih; Yarmaliza, Yarmaliza; Reynaldi, Fitrah; Zakiyuddin, Zakiyuddin; Syahputri, Veni Nella; Susanna, Dewi (UI Scholars Hub, 2022)
Background. Indonesia is one of the countries affected by the COVID-19 pandemic. The elderly are the most severely affected group due to the severity/morbidity and mortality of COVID-19 disease. West Aceh Regency is one of the red zone areas with confirmed cases of COVID-19. Aim. This study aims to analyze the COVID-19 prevention behavior in the elderly group. Method. This type of research was descriptive-analytic with a quantitative approach. The sampling technique used total sampling. The data collection used a questionnaire instrument. This study's data analysis used three univariate, bivariate, and multivariate analyses. Results. The results showed that 69.8% of the elderly had less Perceived Susceptibility but had good COVID-19 prevention. 64.7% of the elderly with good Perceived Severity but have less prevention. 63.6% of respondents have good Perceived Benefits and good COVID-19 prevention. 69.1% of respondents have fewer Perceived Barriers but have good COVID-19 prevention and 69.1% have good Cues to action plus good COVID-19 prevention. The dominant factors are Perceived Severity (OR value 2.77) and Perceived Barriers (OR value of 2.76). Conclusion. Health Belief Model could lead to behavioral change to prevent the potential for COVID-19 among the elderly.